Femme Type : A book celebrating women in the type industry - Weaver, Amber (London : People of Print, 2019)
Marques, Lilly ; Afshar, Sahar ; Rauch, Natalie ; Rohde, Charlotte ; Correia, Joana ; Yun, Lynne ; Typelab ; Urbina Peã, Isabel ; Turkenich, Liron Lavi ; Chaccur, Marina ; Twins, Yarza ; Matos, Rita ; Yeon Hwang, Hui ; Bianchini, Caterina ; Cerda, Marta ; Price, Rachel Joy ; Nugue, Sandrine ; Plönnigs, Inga ; Savoie, Alice ; Carras, Erica ; Lin, Letitia ; Hello this is Kae ; Liolio, Anastasia ; My Name is Wendy ; Touli, Tina ; Papaelias, Amy ; Lopez, Nuria ; Kahl, Julia ; Duje, Ana ; Robinson, Brook ; Liao, TienMin ; Ramos, Maria ; Gerlach, Verena ; Olsen, Johanne Lian ; Möbel Type Foundry ; Tinnes, Andrea ; Hagmann, Sibylle ; Martin, Leonie ; Brunner, Laura ; Saxena, Pooja ; Doreuli, Maria ; Meseguer, Laura ; Chahine, Nadine ; Fuerte, Veronica ; Sparrow, Shanti ; Gawin, Marta
boek